A novel 2D perovskite as surface "patches" for efficient flexible perovskite solar cells. Issue 16 (7th April 2020) - Yangi, Longkai; Li, Yiwen; Pei, Yaxi; Wang, Jiaqin; Lin, Hong; Li, Xin
Abstract : High-efficiency flexible perovskite solar cells based on a novel mixed-cation 2D perovskite passivating FA-based perovskite absorber. Abstract : Two-dimensional (2D) perovskites are promising passivating materials to improve the photovoltaic performance and stability of lead halide perovskite solar cells (PSCs). In this work, we report a novel mixed 2D perovskite based on phenylformamidinium (PFA) cations and formamidinium (FA) cations as surface "patches" to stabilize an FA-based perovskite, whose formula is Cs0.05 Rb0.05 (FA0.83 MA0.17 )Pb(I0.95 Br0.05 )3 . The mixed-cation 2D perovskite "patches" can be obtained by dropping a PFA iodide (PFAI) solution (≥6 mg mL −1 ) dynamically on the FA-based perovskite film surface. The mixed-cation 2D perovskite can effectively reduce perovskite surface defects and suppress the recombination at the interface between the perovskite layer and the hole transport layer, which results in improved device performance and thermal stability. Our champion flexible PSC presents a power conversion efficiency (PCE) of 19.89%, which is one of the highest reported values for single-junction flexible PSCs to date. The unencapsulated flexible device with the "patches" retains 70.4% of its initial efficiency after 1000 h at 85 °C in a N2 environment. Our new strategy demonstrates a highly promising way to passivate the FA-based perovskite surface for highly efficient PSCs, particularly flexible PSCs.